2018
DOI: 10.3389/fimmu.2018.01639
|View full text |Cite
|
Sign up to set email alerts
|

Human Liver Stem Cell-Derived Extracellular Vesicles Prevent Aristolochic Acid-Induced Kidney Fibrosis

Abstract: With limited therapeutic intervention in preventing the progression to end-stage renal disease, chronic kidney disease (CKD) remains a global health-care burden. Aristolochic acid (AA) induced nephropathy is a model of CKD characterised by inflammation, tubular injury, and interstitial fibrosis. Human liver stem cell-derived extracellular vesicles (HLSC-EVs) have been reported to exhibit therapeutic properties in various disease models including acute kidney injury. In the present study, we aimed to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 53 publications
5
71
0
Order By: Relevance
“…Therefore, EV-associated proteins may implement the biological activity of regulatory RNAs present in the EVs. 10,11 In conclusion, the results of the present study indicated that EVs released from HLSCs exert anti-inflammatory and anti-fibrotic effects in a model of chronic liver disease by carrying molecules that may modulate genes involved in fibrosis. Fibrosis is an abnormal mechanism of tissue repair after repeated and sustained injuries that has common pathways in different organs.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Therefore, EV-associated proteins may implement the biological activity of regulatory RNAs present in the EVs. 10,11 In conclusion, the results of the present study indicated that EVs released from HLSCs exert anti-inflammatory and anti-fibrotic effects in a model of chronic liver disease by carrying molecules that may modulate genes involved in fibrosis. Fibrosis is an abnormal mechanism of tissue repair after repeated and sustained injuries that has common pathways in different organs.…”
Section: Discussionmentioning
confidence: 53%
“…We previously showed in two different models of chronic kidney diseases that the anti-fibrotic effect of EV-HLSCs is linked to the presence of microRNA (miRNA) patterns targeting the fibrotic genes. 10,11 In particular, we found that EV-HLSCs contain miRNA-29a, the let-7 family, miRNA-30a, miRNA-24, and miRNA-21, which are known to target Collagen I, Snail, and the FAS ligand. 11 In the present study, we performed proteomic analyses of EV-HLSCs showing the presence of several anti-inflammatory proteins that may contribute to the final anti-fibrotic effect by downregulating inflammation.…”
Section: Discussionmentioning
confidence: 93%
“…69 However, the advantages in the use of EVs engineered with Klotho have not been reported yet. In the present study, Klotho was loaded onto fibroblast EVs, a Klotho negative EV source previously described as non-effective in renal repair, 70,71 and the inefficacy of naive EVs in AKI was reverted in parallel with the restoration of its endogenous levels. Moreover, the effect of recombinant Klotho administered alone at a dose comparable with that of uEVs (1 pg/mouse) did not exert any regenerative effect.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, NLRP3 or Caspase-1 deficiency showed protective effects against renal injury in the mouse model of acute AAN, suggesting the involvement of NLRP3 signaling in the pathogenesis of AAN [74]. Inflammation in a rat model of AA was also reported by Kholia et al [75]. and in HK-2 cells by Wang et al [65].…”
Section: Aa Induces Inflammatory Responsementioning
confidence: 67%